2018
DOI: 10.3389/fmicb.2017.02697
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Virulence Genes and Antimicrobial Resistance Profiles of Salmonella Serovars from Retail Beef in Selangor, Malaysia

Abstract: The aim of the present study was to investigate the prevalence of Salmonella spp., Salmonella Enteritidis and Salmonella Typhimurium in retail beef from different retail markets of Selangor area, as well as, to assess their pathogenic potential and antimicrobial resistance. A total of 240 retail beef meat samples (chuck = 60; rib = 60; round = 60; sirloin = 60) were randomly collected. The multiplex polymerase chain reaction (mPCR) in combination with the most probable number (MPN) method was employed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
70
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 29 publications
19
70
3
3
Order By: Relevance
“…MDR Salmonella has been observed in other countries such as Malaysia (Thung et al, 2018). MDR Salmonella isolates are considered to be highly virulent than non-MDR (Thung et al, 2018) and this finding was a major concern in the current study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…MDR Salmonella has been observed in other countries such as Malaysia (Thung et al, 2018). MDR Salmonella isolates are considered to be highly virulent than non-MDR (Thung et al, 2018) and this finding was a major concern in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…This is worrying because some antibiotics are recommended drugs for the treatment of salmonellosis (Hirose et al, 2001). MDR Salmonella has been observed in other countries such as Malaysia (Thung et al, 2018). MDR Salmonella isolates are considered to be highly virulent than non-MDR (Thung et al, 2018) and this finding was a major concern in the current study.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Along with issues concerning antibiotic resistance in clinical settings, there has been increased interest in antimicrobial resistance genes (ARGs) in food. ARGs have been detected in retail meat and seafood sources (Thung et al, 2017), foods other than meat (Maka, Mackiw, Sciezynska, & Popowska, 2015), as well as poultry and swine (Chuanchuen & Padungtod, 2009). This study indicated the diversity and abundance of ARGs in food sources.…”
Section: Introductionmentioning
confidence: 99%